PENGARUH ANGKA HARAPAN HIDUP DAN TINGKAT PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI DI SUMATERA BARAT PADA TAHUN 2010-2019 - Hanifa Hanifa; Irsad Irsad (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Economic growth has decreased in West Sumatra Province, while life expectancy has fluctuated and in 2017 it increased and for the average length of schooling it increased. Economic growth should have decreased life expectancy and the average length of schooling has also decreased, while in West Sumatra Province in 2010-2019 it was the opposite. The purpose of this discussion is to find out how much life expectancy and education level affect economic growth in West Sumatra in 2010-2019. The type of research that the author uses is a type of field research (Field Research) to obtain data from the problems studied. The data collection technique that the author uses is a documentation technique for the report on Life Expectancy, Average Years of Schooling and Economic Growth of West Sumatra in 2010-2019. Data processing is carried out quantitatively by using the analytical method using Multiple Linear Regression. Based on the results of this study, the province of West Sumatra in 2010-2019 shows that (1) life expectancy and education level partially have a negative influence on economic growth, each at 5.832 for life expectancy and 8.664 for level of education. (2) simultaneously it is clearly proven that the variable life expectancy and education level have a positive effect on economic growth by having a figure of 75,092.